THE EFFECT OF PICTURE MEDIA ON WRITING SKILLS OF EXPOSITION NOTES IN CLASS VIII MADRASAH TSANAWIYAH AL HIDAYAH DEPOK - Endang Sulistyaniningsih; Fatimah Fatimah (Universitas Indraprasta PGRI, 2019)
Abstract: The purpose of this study was to determine the effect of image media on Indonesian language subjects especially in exposition essay writing skills on class VIII Madrasah Tsanawiyah Al Hidayah Depok. The research method used to analyze is the pretest method, in the form of an exposition essay test before using image and posttest media, in the form of exposition essay tests after using image media. On the pretest test the average score was 73 and the posttest test obtained an average score of 82. The average scores of the two groups were classified into the categories